Associations between childhood maltreatment and overt aggression in depressed adolescents: the mediating effect of alexithymia and insomnia - Wang, Jiawei; Liu, Lewei; Zhou, Sanhua; Zhao, Lili; Wu, Qianqian; Sun, Tiantian; Zhang, Nali; Wei, Xuemei; Xia, Lei; Zhao, Feng (Frontiers in Psychiatry, 2025)
BackgroundOvert aggression may be associated with childhood maltreatment (CM), insomnia, and alexithymia, but the underlying mechanisms of these associations have not been fully explored in adolescents with major depressive disorder (MDD). Therefore, the present study aimed to deeply analyze the relationships between overt aggression and CM, insomnia, and alexithymia in adolescents with MDD, to reveal the mediating mechanisms, and to provide a theoretical basis for clinical interventions.MethodsFrom December 2024 to December 2025, this study included 251 adolescents with MDD. The Modified Overt Aggression Scale (MOAS), the 17-item Hamilton Depression Rating Scale (HAMD-17), the Childhood Trauma Questionnaire (CTQ), the Insomnia Severity Index Scale (ISI), and the Toronto Alexithymia Scale (TAS-20) were used to assess the adolescents’ overt aggression, depression, CM, insomnia, and alexithymia. Additionally, we employed the PROCESS macro program to examine the mediating role of insomnia and alexithymia between CM and overt aggression.ResultsThe prevalence of overt aggression in adolescents with MDD was 66.1%. The regression analyses showed that age (Beta = -0.761, t = -2.967, P = 0.003), depression (Beta = 0.183, t = 2.676, P = 0.008), CM (Beta = 0.132, t = 4.048, P < 0.001), and alexithymia (Beta = 0.092, t = 1.990, P = 0.048) were independent correlates of overt aggression. When CTQ subscale scores involved in the regression model, age (Beta = -0.829, t = -3.257, P = 0.001), depression (Beta = 0.184, t = 2.618, P = 0.009), emotional abuse (Beta = 0.372, t = 4.081, P < 0.001), and insomnia (Beta = 0.170, t = 2.054, P = 0.041) were independent correlates. Moreover, alexithymia and insomnia played a chain mediating role between CM and overt aggression.ConclusionThe risk of overt aggression is significantly higher in depressed adolescents and is significantly associated with CM, insomnia, and alexithymia. Additionally, insomnia and alexithymia may play a mediating role between CM and overt aggression. Given these findings, comprehensive interventions for depressed adolescents with adverse childhood experiences, insomnia, and alexithymia, should be emphasized in clinical practice to effectively reduce their risk of overt aggression.